Service Quality and Students’ Satisfaction in Higher Education Institutions: Nepali Students’ Experiences and Perceptions - Adhikari, Santosh (Prithvi Academic Journal, 2024)
Service quality in higher education has become a topic of growing interest in recent years. As a competition among higher education institutions around the world has increased, there has been a growing focus on providing high-quality services to students in order to attract and retain them. Thus, it is required to evaluate their satisfaction on the basis of service quality provided by higher education institutions. This study examines students’ satisfaction on service quality of Prithvi Narayan Campus (PNC), Pokhara. Thus, the main objective of the study is to analyse the major influencing factors of non-academic aspects of service quality, to measure the relationship of non-academic aspects of service quality with students’ satisfaction, and to analyse the impact of non-academic aspects on students’ satisfaction on service quality. Using the multi-phase sampling technique, both descriptive and inferential statistic was used to meet the objectives of this study. The overall students’ satisfaction towards the service quality provided by PNC is more than average. The study concludes that there is a low degree of positive correlation between non-academic aspects of service quality and students’ satisfaction. For non-academic aspects of service quality, only extra-curricular activities show a statistically significant impact on students’ satisfaction.